A new design of substrate integrated waveguide diplexer using complementary split ring resonators. Issue 8 (11th April 2019) - Mohammadi, Pejman; Gheibi, Rana
Abstract: Design method for achieving the acceptable electrical responses (isolation and impedance matching) of a mixer in two‐close frequency with substrate integrated waveguide (SIW) is presented. SIW diplexer with complementary split ring resonators and an open stub is proposed. The SIW loaded diplexer is operated below the cutoff frequency of the equivalent waveguide for SIW; therefore, the size of the structure is compacted. Input and output ports matching are realized in the light of open microstrip stub. The diplexer with optimum dimensions is designed and fabricated. The measurement results verified the design procedures. They also show that operation frequencies are very close together, and also the proposed structure is suitable for long term evolution frequency bands.